Electrochemical Characterization of Novel Polyantimonic-Acid-Based Proton Conductors for Low- and Intermediate-Temperature Fuel Cells - Olga Yu. Kurapova; Pedro M. Faia; Artem A. Zaripov; Vasily V. Pazheltsev; Artem A. Glukharev; Vladimir G. Konakov (Applied Sciences, 2021)
The development of novel proton-conducting membrane materials for electrochemical power units, i.e., low temperature fuel cells (FCs), efficiently working up to 300 °C, is a critical problem related to the rapid shift to hydrogen energy. Polyantimonic acid (PAA) is characterized by high conductivity, sufficient thermal stability and can be regarded as a prospective proton-conducting material. However, the fabrication of bulk PAA-based membranes with high proton conductivity remains a challenging task. In the present work, for the first time, the authors report the investigation on proton conductivity of bulk PAA-based membranes in the temperature range 25–250 °C, both in dry air and in moisturized air. Using PAA powder and fluoroplastic as a binder, fully dense cylindrical membranes were formed by cold uniaxial pressing. The structures of the PAA-based membranes were investigated by SEM, EDX, XRD and Raman techniques. STA coupled with in situ thermo-XRD analysis revealed that the obtained membranes corresponded with Sb2O5·3H2O with pyrochlore structure, and that no phase transitions took place up to 330 °C. PAA-based membranes possess a high-grain component of conductivity, 5 × 10−2 S/cm. Grain boundary conductivities of 90PAA and 80PAA membranes increase with relative humidity content and their values change non-linearly in the range 25–250 °C.